USULAN PENERAPAN LEAN SIX SIGMA, FMEA DAN FUZZY UNTUK MENINGKATKAN KUALITAS PRODUK BOTOL SABUN CAIR - Mario Sarisky Dwi Ellianto; Purnomo Budi Santoso; Achmad As'ad Sonief (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract The goal of lean six sigma method is to solve the problems of waste, especially defect. The goal of failure mode and effect analysis (FMEA) method is to be able to identify potential failures in the production process of e.g. liquid soap bottle in order to reduce production failure and to have reference from FMEA highest risk priority number for corrective actions. The goal of fuzzy method is to improve priority risks of FMEA method. By using fuzzy method the priority risks with the same value can be eliminated so that only one highest value can be used as a reference for corrective action. Result of lean six sigma method are four types of critical defects i .e. dirty black, lines in the wall of the bottle, neck narrowed / clogged, and uneven surfaces. One result of the FMEA calculation with the highest risk priority number (RPN) is dirty black defect.This is due to less attention to the composition of the material and contamination / burnt crust. The highest score of RPN is 48 and ranked as the first priority for actions. While result of fuzzy calculations is the highest fuzzy risk priority number (FRPN) with value of 3.327831. This is caused by dirty black defect due to less attention to the composition of the material. Therefore from these results of the highest causes of defects can be used as a reference for corrective action.